Overview of Knowledge, Attitude and Behavior of Pregnant Women in Self Monitoring of Fetal Movement - Nafisah, Nadila Zahra; Widiasih, Restuning; Mamuroh, Lilis (CV. Global Health Science Group, 2025)
Fetal movement monitoring is one of the most important things to assess fetal well-being which can be done independently by pregnant women. However, studies on the ability of pregnant women to conduct self-monitoring of fetal movements were still limited. Objective: The purpose of this study was to determine the description of knowledge, attitude and behavior of pregnant women in self-monitoring of fetal movements in Sukawening District, Garut. This study used secondary data obtained from the main research entitled